Penggunaan Kalium Permanganat (KMnO4) Untuk Menunda Pematangan Buah Pepaya (Carica papaya L. var. Bangkok) - Mukarlina, Arini, Riza Linda (Jurnal Protobiont, 2015)
Papaya fruit (Carica papaya L.) is one of the horticultural products that contains a high nutritional value. The Papaya generally is easily damaged, so it is necessary to delay its ripening to maintain the quality. One of the methods of delaying the ripening of papaya is by using KMnO4 with absorbent material of sawdust. This research aimed to find out the influence of KMnO4 as the material for delaying papaya ripening. The research was conducted from March 2015 until May 2015 in the Laboratory of Biology, Faculty of Mathematics and Natural Sciences, and the Laboratory of Agricultural Produce Technology, Faculty of Agriculture, Tanjungpura University Pontianak. The research used a Completely Randomized Design (CRD) consisting of 6 treatments with a concentration of KMnO4 at0 ppm (A0), 60 ppm (A1), 75 ppm (A2), 90 ppm (A3), 105 ppm (A4) and 120 ppm (A5). The research findings indicated that KMnO4 at 60 ppm treatment affected the period of fruit storage for 12 days, with a weight loss of 7.56% and fruit glucose level at 5.096%.